A computational mechanistic study of Pd(ii)-catalyzed γ-C(sp3)–H olefination/cyclization of amines: the roles of bicarbonate and ligand effect. Issue 14 (16th March 2018) - Liu, Jian-Biao; Tian, Ying-Ying; Zhang, Xin; Wang, Lu-Lin; Chen, De-Zhan
Abstract : The bicarbonate aids the C–H activation and abstracts the β-proton in the reductive elimination via a PCET mechanism. Abstract : The detailed mechanism of palladium-catalyzed γ-C(sp 3 )–H olefination/cyclization of triflyl-protected amines was investigated by density functional theory (DFT) calculations. The olefinated intermediate was initially formed in the first catalytic cycle involving ligand exchange, bicarbonate-assisted C(sp 3 )–H bond cleavage, alkene insertion and 'reductive β-hydride elimination'. The following syn -addition and reductive elimination furnish the aza-Wacker product. The first step of reductive elimination is the rate-determining step. The mechanism unveils the important roles of bicarbonate: aiding the C–H activation and abstracting the β-proton in the second step of reductive elimination. The parallel bridging mode in the metal-olefin intermediate facilitates the syn -addition, explaining the experimentally observed stereoselectivity. The effect of the monodentate pyridine-based ligands is also discussed.